Use of oil palm waste as a renewable energy source and its impact on reduction of air pollution in context of Malaysia - Begum S.; Kumaran P.; Jayakumar M. (Institute of Physics Publishing, 2023)
One of the most efficient and effective solutions for sustainable energy supply to supplement the increasing energy demand and reducing environment pollution is renewable energy resources. Malaysia is currently the world's second largest producer and exporter of palm oil and 47% of the world's supply of palm oil is produced by this country. Nearly 80 million tonnes of Fresh Fruit Bunches (FFB) are processed annually in 406 palm oil mills and are generating approximately 54 million tonnes of palm oil mill effluent (POME), known to generate biogas consisting of methane-a Green House Gas (GHG) identifiable to cause global warming. This is 21 times more potent GHG than CO2. These two major oil palm wastes are a viable renewable energy (RE) source for production of electricity. If the two sources are used in harnessing the renewable energy potential the pollution intensity from usage of non-renewable sources can also be reduced significantly. This study focused on the pollution mitigation potential of biogas as biogas is a renewable energy. Utilization of this renewable source for the production of electricity is believed to reduce GHG emissions to the atmosphere. Published under licence by IOP Publishing Ltd.